Volume 5: Manufacturing Materials and Metallurgy; Ceramics; Structures and Dynamics; Controls, Diagnostics and Instrumentation; 1982
DOI: 10.1115/82-gt-87
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Turbine Deposition Observations From Residual and Simulated Residual Oil Studies

Abstract: Burning residual oil in utility combustion turbines and the consequent deposition on blades and vanes may adversely affect reliability and operation. Corrosion and deposition data for combustion turbine materials have been obtained through dynamic testing in pressurized passages. The deposition produced by the 1900°F (1038°C) combustion gases from a simulated and a real residual oil on cooled Udimet 500 surfaces is described. Higher deposition rates for the doped fuel than for the real residual oil raised ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

1987
1987
1987
1987

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…Consequently, a DEC screening approach was formulated to independently control and evaluate as many DEC variables as possible with available resources. The DEC test approach and facility developed in this program are advancements of those previously used to evaluate turbine degradation based in 600 hr of residual oil tests (Whitlow et al, 1982) and 1400 hr of coal-derived liquid tests (Spengler et al, 1983). Figure 2 is a schematic of the DEC test facility.…”
Section: Approachmentioning
confidence: 99%
“…Consequently, a DEC screening approach was formulated to independently control and evaluate as many DEC variables as possible with available resources. The DEC test approach and facility developed in this program are advancements of those previously used to evaluate turbine degradation based in 600 hr of residual oil tests (Whitlow et al, 1982) and 1400 hr of coal-derived liquid tests (Spengler et al, 1983). Figure 2 is a schematic of the DEC test facility.…”
Section: Approachmentioning
confidence: 99%
“…The transfer of solid particles to the blade surface is controlled by a number of deposition mechanisms: inertia, eddy diffusion, Brownian motion and thermophoresis. Previous work [10,67,90,153,154,157] has shown that particles with diameters less than 0.01 μιη are transported to the blades mainly by Brownian diffusion. For particles in the size range 0.01 to 1 μπι ^he main mechanisms are eddy diffusion and thermophoresis, while supermicron particles are transported to the blades by inertial forces, resulting in erosion, as shown in figure 18.…”
Section: An Extended Summarymentioning
confidence: 96%
“…Καθώς ο ρυθμός άφιξης στην κοιλιά είναι μεγαλύτερος, τό κατάλοιπο εκεί είναι παχύτερο [157]. Υπενθυμίζεται ότι τα μεγαλύτερα σωματίδια προσκολλώνται στην επιφάνεια του πτερυγίου λόγω του κολλώδους στρώματος που σχηματίζουν τά μικρότερα σωματίδια Ο Carpenter [16] επισημαίνει τους παραπάνω μηχανισμούς εναπόθεσης και προτείνει συστήματα ψύξης με νερό ή με έγχυση αέρα στο πτερύγιο για τήν μείωση τής εναπόθεσης.…”
Section: ερευνητικά αποτελέσματα κατ υπόβαθροunclassified
See 1 more Smart Citation